Cosa Nostra at the conquest of Rome (Rivista di Studi e Ricerche sulla criminalità organizzata, 2020)
The presence of the Sicilian mafia in Lazio Region is an ancient story. The arrivals of high-ranking Mafia exponents, who are concentrated around the capital, date back to the 1950s. That of Natale Rimi represents the case that better than others illustrates the strategic nature of the Cosa Nostra in Rome. A summary of the facts is proposed, followed by the testimony collected by the Anti-mafia Parliamentary Commission of the then regional councilor Antonio Muratore, responsible for hiring a boss's son employee to the Region.
Keywords: Cosa Nostra, Rome, mafia strategy, Lazio Region, recruitment